Analysis of Adolescent Sexual Behavior Based on The Influence of Family and Environment - Intan Syahrani; Fitriyani Fitriyani (Universitas Muhammadiyah Semarang, 2026)
Adolescent sexual behavior has emerged as a critical issue in public health, particularly in the digital era and amid rapid social change. This study aimed to examine the influence of family factors, namely parenting style and parental marital status, as well as environmental factors, especially peer influence, on adolescent sexual behavior in Pekalongan Regency, 2025. A quantitative research design with a cross-sectional approach was employed. The study population included high school students across Pekalongan Regency, and cluster random sampling was used to produce a sample of 393 respondents. Data were analyzed using Chi-square tests for bivariate analysis and multiple logistic regression for multivariate analysis. The results revealed that peer influence showed a significant relationship with adolescent sexual behavior, where adolescents who were strongly influenced by peers were nearly twice as likely to engage in risky sexual activity compared to those less affected by peers. In contrast, parental marital status and parenting style showed no significant association with sexual behavior. Furthermore, regression analysis confirmed that among the variables studied, peer influence was the only factor with a significant effect, indicating its role as the strongest predictor of risky sexual behavior. In conclusion, peer influence constitutes the most influential factor shaping adolescent sexual behavior in Pekalongan Regency. Efforts to prevent risky sexual activity among adolescents should therefore emphasize strengthening positive peer roles, encouraging constructive group activities, and ensuring comprehensive support from schools and families.